One-Pot Synthesis of Polynuclear Indole Derivatives by Friedel–Crafts Alkylation of γ-Hydroxybutyrolactams - Vladimir T. Abaev; Nicolai A. Aksenov; Dmitrii A. Aksenov; Elena V. Aleksandrova; Alesia S. Akulova; Igor A. Kurenkov; Alexander V. Leontiev; Alexander V. Aksenov (Molecules, 2023)
The Friedel–Crafts reaction of novel 3,5-diarylsubstituted 5-hydroxy-1,5-dihydro-2H-pyrrol-2-ones was used for low cost, one-pot preparation of polycyclic indole derivatives structurally similar to Ergot alkaloids.